Evaluation of MTIP, MPTCP and MPQUIC for a Time-Sensitive Application. - Rico, Delia; Luque-Schempp, Francisco; Merino-Gómez, Pedro (IEEE, 2025)
This paper compares the behavior of the Multi-connection Tactile Internet Protocol (MTIP) with two other well-known multipath protocols, Multipath TCP (MPTCP) and Multipath QUIC. The evaluation focuses on the effectiveness of the protocols in scenarios involving the remote control of a quadruped robot during emergency rescue operations. The study aims to determine how these protocols perform under various network conditions, including stable connections, link failures, and typical 5G network impairments. MTIP leverages network programmability to dynamically adapt to changing conditions, maintaining low latency without compromising the expected reliability for time-sensitive applications. MTIP dynamic path management provides significantly better results for the target use case compared to the other protocols, especially in adverse environments. This paper contributes to understanding how multipath communication can enhance the execution of time-sensitive applications.
Keywords: Protocolos de comunicaciones; Multipath protocols; Time-sensitive applications; MPTCP; Multipath QUIC; MTIP; 5G; Tactile internet